VD_FINDINFO Arrêt / 2014 / 924 vom 5. November 2014 - VD Tribunal cantonal (2014)
REJET DE LA DEMANDE, DROIT DE GARDE, RÉSIDENCE HABITUELLE, PROVISOIRE, DÉPART D'UN PAYS | 301a al. 2 let. a CC, 310 CC, 445 CC, 450 CC